ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MATERI LINGKARAN PADA PESERTA DIDIK KELAS VIII - Sarif Alit Budiman; Dinny Mardiana; Deti Ahmatika (Universitas Islam Nusantara, 2022)
The purpose of the study was to find out the description of the mathematical problem solving abilities of VIII-C class PENIDA Katapang Junior High School students in circle material. The research uses a qualitative approach with a descriptive method. Data collection techniques using documents, tests and in-depth interviews. The research subjects were six people consisting of students in the upper, middle and lower categories. The research subjects were determined by purposive sampling technique by using documents study. To find out the problem solving ability of students using test questions that have been validated. In-depth interviews were conducted to find out the low problem solving abilities of student and their causes. The results show that the problem-solving abilities of students were included in the weak category at each level, namely: (1) for the upper category, it was sufficient; (2) for the medium category including less; and (3) for the lower category including very less. So that the overall student problem solving ability is at a low level.